Búsqueda de Salmonella entérica en tortugas semiacuaticas del Centro de Atención y Valoración de Fauna Silvestre del Área Metropolitana. (2008)
Estudios previos realizados en otros países, indican que las tortugas que conviven como mascotas con los humanos, pueden ser reservorios de Salmonella, bacteria que produce cuadros clínicos severos en los humanos y en las tortugas inmunosuprimidas.| ABSTRACT: Recent studies in other countries show that turtles used as pets in human environments can transmit Salmonella. This type of bacteria can cause serious health problems in humans and to the turtles as well. The objective of the present research was to find Salmonella enterica among turtles that are received in the Centro de Atención y Valoración del Area Metropolitana del Valle del Aburrá (CAV), these animals came after being in contact with humans, and being natural reservoirs for Salmonella could become the source of infection. Detection of Salmonella spp was carried out in feces samples using bacteriological cultures and PCR for specific DNA tests for genus and serotype.